Temporal Relationship Between Changes in Serum Calcium and Hypercholesteremia and Its Impact on Future Brachial-Ankle Pulse Wave Velocity Levels - Meng, Xing; Han, Tianshu; Jiang, Wenbo; Dong, Fengli; Sun, Hongxue; Wei, Wei; Yan, Yageng (Frontiers in Nutrition, 2021)
Background: High levels of serum calcium and cholesterol are important risk factors of cardiovascular disease (CVD), which frequently influence each other during the development of CVD. However, few studies have examined their temporal relationship to confirm the precursor, and it is still largely unknown whether and how their temporal relationship would influence the development of CVD. This study aims to establish the temporal relationship between changes in serum calcium and cholesterol using longitudinal cohort data, and examine whether this temporal relationship influenced the arterial elasticity indicated by brachial-ankle pulse wave velocity (baPWV). Methods: This is a cohort study with a sample of 3292 Chinese participants (aged 20–74 y) with 5.7 years follow-up. Serum calcium and cholesterol were measured at baseline and follow-up survey. The cross-lagged path analysis was used to examine their temporal relationship, and mediation analysis was performed to evaluate potential mediating effect. Results: The cross-lagged path coefficients (β2 values) from baseline serum calcium to follow-up cholesterol was significantly greater than path coefficients (β1 values) from baseline cholesterol to follow-up serum calcium (β2=0.110 versus β1=0.047; P=0.010) after adjusting for multiple covariates. The path coefficients from baseline serum calcium to follow-up cholesterol in the participants with high baPWV was significantly greater than the participants with low baPWV (β2=0.155 for high baPWV and β2=0.077 for low baPWV, P=0.028 for the difference between β2 values). Moreover, cholesterol partially mediated the association between higher serum calcium and greater subsequent baPWV values, the percentage of the total effect mediated by cholesterol was estimated at 21.7%. Conclusion: Our ﬁndings indicate that increased serum calcium precedes increased in serum cholesterol, and this temporal relationship may contribute to the development of higher baPWV levels.